UJI EFEKTIVITAS JAMUR Metarhizium anisopliae Cps.T.A ISOLAT LOKAL TERHADAP HAMA RAYAP (Coptotermes curvignathus) - Khairunnisa '; Atria Martina; Titrawani ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Termites is one of the major pest of oil palm plantations on peatlands. Termite control is generally performed using chemical insectisides. Several chemical insecticides can inhibit termite attack effectively but not effeciently used because it has many negative effects. The negative effect of chemical insecticides can be reduced using biological agents such as entomopathogenic fungus. This research aimed to determine the effectivenes and the best formulation of local isolate of M. anisopliae Cps.T.A and with the addition of 10% zeolite in controling C. curvignathus. The reaserch used Complete Randomized Design (CRD) with three treatments and eight replications. The results showed that density of M. anisopliae Cps.T.A with addition of 10% zeolite was 2,25 x 108 spora/g and M. anisopliae Cps.T.A was 2,50 x 108 spora/g. Germination of M. anisopliae Cps.T.A with 10% zeolite was 91,2% and M. anisopliae Cps.T.A was 88,1%. The treatment of M. anisopliae Cps.T.A produced the highest mortality (100%) of M. anisopliae Cps.T.A with 51% zeolite, whereas the mortality of termite control was only 16%.